PENGARUH LITERASI KEUANGAN TERHADAP KINERJA KEUANGAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI KELURAHAN ANAIWOI KABUPATEN KOLAKA - Nuraisyah, Nuraisyah; Triani, Neks; Syahrir, Sasmita Nabila (Komunitas Manajemen Kompetitif, 2025)
This research investigate show financial literacy influences the financial performance of MSMEs located in Anaiwoi Village, Kolaka Regency. Utilizing a quantitative methodology, data was gathered through questionnaires administered to local MSME proprietors. The study targets all MSMEs operating within Anaiwoi Village as its population, with a total of 40 respondents chosen via the total sampling method. Findings reveal that financial literacy significantly and positively contributes to the financial outcomes of the seenter prises. Businessowners with greater financial knowledge tend to manage their finances more effectively, resulting in improved performance. The study suggests that MSME actors should deepen their financial understanding to ensure long-term business viability. Furthermore, the insights may assist governmental bodies and relevant institutions in formulating programs to elevate financial literacy among small business operators.Keywords: Financial Literacy, Financial Performance, MSMEs